2010
DOI: 10.2341/09-202-l
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Oxalate Desensitizer on the Durability of Resin-Bonded Interfaces

Abstract: Clinical RelevanceDespite oxalate desensitizer showing a decrease in the rate of resin-dentin bond degradation over time, it compromised the baseline bond strength of etch-and-rinse adhesives to dentin. Further investigation regarding reliability of the combination of oxalate desensitizers and etch-and-rinse adhesives is required prior to implementation of this approach in the clinical routine. SUMMARYPotassium oxalate desensitizers were previously shown to effectively reduce the immediate permeability of resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 31 publications
2
15
0
Order By: Relevance
“…After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionsupporting
confidence: 64%
See 3 more Smart Citations
“…After 2 years, they also showed that the potassium oxalate may adversely affect the baseline hardness of etch-and-rinse adhesives [34]. Therefore, in accordance with these previous studies [21,[29][30][31][32][33][34], it can speculate that crystal precipitation on the etched dentin surface impaired the adequate hybrid layer formation.…”
Section: Discussionsupporting
confidence: 64%
“…Silva et al [21] also evaluated whether the effect of the combined application of oxalate with etch-and-rinse adhesives interferes with the durability of resin-dentin bonds when using two-and three-step etch-and-rinse adhesives. They used the microtensile method in the laboratory and showed that, despite oxalate desensitizer being shown to contribute to the reduction of resin-dentin bond degradation over time, it compromised the baseline bond strength to the teeth that received potassium oxalate after acid etching.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[10] However, it was observed a reduction in the bond strength to the teeth that received oxalic acid after aging. [11]…”
Section: Introductionmentioning
confidence: 99%